2007
DOI: 10.1017/s1049096507071028
|View full text |Cite
|
Sign up to set email alerts
|

Early Voting and Turnout

Abstract: Early or convenience voting—understood in this context to be relaxed administrative rules and procedures by which citizens can cast a ballot at a time and place other than the precinct on Election Day—is a popular candidate for election reformers. Typically, reformers argue that maximization of turnout is a primary goal, and reducing barriers between voters and the polls is an important method for achieving higher turnout. Arguments in favor of voting by mail, early in-person voting, and relaxed absentee requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
76
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(80 citation statements)
references
References 18 publications
2
76
1
Order By: Relevance
“…We also do not yet understand 7 Smets and van Ham 2013. 8 Gronke, Galanes-Rosenbaum, and Miller 2007;Stein and Garcia-Monet 1997. 9 Wolfinger and Rosenstone 1980;Wolfinger, Highton, andMullin 2005.…”
mentioning
confidence: 99%
“…We also do not yet understand 7 Smets and van Ham 2013. 8 Gronke, Galanes-Rosenbaum, and Miller 2007;Stein and Garcia-Monet 1997. 9 Wolfinger and Rosenstone 1980;Wolfinger, Highton, andMullin 2005.…”
mentioning
confidence: 99%
“…More instrumental methods to entice young people back to the polls include making the polls more accessible by early voting (Gronke, 2007;Nichols, 2010), more liberalized absentee voting provisions (CIRCLE, 2010c), electoral day registration (Knack and White 2002), and all-mail voting, as occurs in Oregon and Washington (Southwell, 2009). CIRCLE has shown that states that allowed for Election Day registration averaged 59% turnout among 18-19 year olds, as compared to 50% in other states (Kawashima-Ginsberg et al, 2009).…”
Section: Possible Remediesmentioning
confidence: 99%
“…In response to this observation, jurisdictions across the United States are embracing methods of "convenience voting," such as noexcuse absentee balloting and voting in person before Election Day. Indeed, over the past two decades, casting ballots other than at the precinct place on the day of an election has become commonplace in American politics (Gronke, Galanes-Rosenbaum, & Miller, 2007;Gronke et al, 2008). Among the variety of convenience voting options presently in use, there is a " [r]apidly expanding list" of U.S. jurisdictions that offer early in person (EIP) balloting opportunities to their electorates (Gronke et al, 2008, p. 441).…”
Section: Introductionmentioning
confidence: 99%
“…Federal courts even acknowledged recently that minority and low-income voters often exhibit higher propensities to vote EIP compared with other socioeconomic and demographic groups (Hasen, 2013; Obama for America [OFA] v. Husted, 2012 [see Preliminary Pretrial Order]). Thus, there is no clear-cut answer to the aforementioned "who" question, and this ambiguity creates a demand for new empirical research on the topic (e.g., Gronke et al, 2007).…”
Section: Introductionmentioning
confidence: 99%